2017
DOI: 10.1002/ange.201706325
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Spirocyclization through C−H Activation and Regioselective Alkyne Insertion

Abstract: A Pd‐catalyzed spirocyclization involving a sequential carbopalladation, intramolecular C−H activation, and a highly regioselective alkyne insertion to afford spirooxindoles and spirodihydrobenzofurans has been achieved. The spirocyclic products were generated in good to excellent yields with complete regiocontrol in a readily scalable procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 54 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Recently, Lautens, Schoenebeck and co-workers reported the synthesis of spiro-fused heterocycles through an intramolecular Heck/C–H activation sequence using specific alkene-tethered aryl iodides (Fig. 1a ) 40 42 . Regarding the starting materials, those substrates might be preferably prepared through an initial palladium-catalyzed Tsuji-Trost allylation of 2-halophenols, which would provide a more efficient and step-economic way 43 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lautens, Schoenebeck and co-workers reported the synthesis of spiro-fused heterocycles through an intramolecular Heck/C–H activation sequence using specific alkene-tethered aryl iodides (Fig. 1a ) 40 42 . Regarding the starting materials, those substrates might be preferably prepared through an initial palladium-catalyzed Tsuji-Trost allylation of 2-halophenols, which would provide a more efficient and step-economic way 43 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Considering the versatility of the in-situ-generated palladacycles III 16 , 26 , 27 , subsequent functionalization including carbene and alkyne insertion should allow for the efficient construction of other classes of novel spiro compounds 29 , 30 , 41 , 42 . To demonstrate this synthetic potential, we performed the reaction of 1a and 2e with two equiv.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Lautens et al reported the annulation reaction between aromatic acrylamides 66 and alkynes 68 to synthesize spirooxindoles 69 (Scheme 24a). 35 The effect of substituents on the substrate was examined. They observed that electron-deficient substituents such as fluoro provided better results than electron-rich substituents.…”
Section: Scheme 16 Rhodium Catalyzed Carboxylate-directed C-h Functio...mentioning
confidence: 99%
“…In 2017, the Lautens group reported a Pd‐catalyzed spirocyclization [Eq. (74‐1)] . This methodology gave access to a variety of spirooxindoles and spirodihydrobenzofurans 74.6 with excellent RR (>20:1).…”
Section: Carbon‐containing Nucleophilesmentioning
confidence: 99%